2015
DOI: 10.1007/s10653-015-9713-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the influence of traffic-related particles in urban dust using sequential selective extraction and oral bioaccessibility tests

Abstract: Urban dust is a heterogeneous mix, where traffic-related particles can combine with soil mineral compounds, forming a unique and site-specific material. These traffic-related particles are usually enriched in potentially harmful elements, enhancing the health risk for population by inhalation or ingestion. Urban dust samples from Estarreja city and traffic-related particles (brake dust and white traffic paint) were studied to understand the relative contribution of the traffic particles in the geochemical beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Since the 1950s, the complex has produced a variety of organic and inorganic compounds, such as nitric acid, aniline, nitrobenzene, chlorate compounds from rock salt, polyurethanes and others. 34,42 In the early years, sulphide ores were used in fertiliser production, which was one of the primary activities of the CCE, yet one of the most polluting for PTEs such as arsenic (As) and Pb. In the late 1990's the area was remediated and industrial wastes containing hazardous materials such as pyrite ashes, mercury-enriched muds, and organochlorine compounds, were buried and sealed near the complex.…”
Section: The Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Since the 1950s, the complex has produced a variety of organic and inorganic compounds, such as nitric acid, aniline, nitrobenzene, chlorate compounds from rock salt, polyurethanes and others. 34,42 In the early years, sulphide ores were used in fertiliser production, which was one of the primary activities of the CCE, yet one of the most polluting for PTEs such as arsenic (As) and Pb. In the late 1990's the area was remediated and industrial wastes containing hazardous materials such as pyrite ashes, mercury-enriched muds, and organochlorine compounds, were buried and sealed near the complex.…”
Section: The Study Areamentioning
confidence: 99%
“…42,46 Hot-dip galvanising for zinc coating or the production and assembly of carbon steel, stainless steel, and aluminium tubing are industrial processes taking place in the CCE likely to emit PTEs to the atmosphere. Indeed, the Zn concentrations reported in different studies focusing on groundwater, soils, home-grown foodstuffs and street dust 34,44,45 suggest elevated levels of environmental Zn in the region.…”
Section: The Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…This group of elements is typical of elements found as waste water outputs from STWs and includes Cd, P, Sb, Cu, Pb, Zn and Cr, and suggests that P concentration increases along with the concentration of the trace element assemble, particularly those associated with road wash-off. In particular, the presence of Sb is a key indicator of STW source as the major likely source is from road dust where it is a component of brake disc linings (Patinha et al 2015). It was found that 206/207 Pb isotope ratios had a strong negative correlation to this group of elements ( Supplementary Information Fig.…”
Section: And 2 Supplementarymentioning
confidence: 99%
“…Mn (50%) in sediments, and Zn (82%) > Cd (58%) > Cu (54%) > Mn (47%) > Pb (45%). The groups of samples containing considerable proportions of PHE in the mobile and reducible phases were likely to be derived from anthropogenic sources, while the less mobile (oxidizable and residual) were linked to geogenic sources (Patinha et al, 2015).…”
Section: Influence Of Solid Phase Matrices In the Respiratory Bioaccementioning
confidence: 99%